Enhancement of Flow-Induced AP-1 Gene Expression by Cyclosporin A Requires NFAT-Independent Signaling in Bone Cells - WORTON, LEAH E. (Cell Mol Bioeng, 2014)
Growing evidence suggests that aging compromises the ability of the skeleton to respond to anabolic mechanical stimuli. Recently, we reported that treating senescent mice with Cyclosporin A (CsA) rescued aging-related deficits in loading-induced bone formation. Given that the actions of CsA are often attributed to inhibition of the calcineurin/NFAT axis, we hypothesized that CsA enhances gene expression in bone cells exposed to fluid flow, by inhibiting nuclear NFATc1 accumulation. When exposed to flow, MC3T3-E1 osteoblastic cells exhibited rapid nuclear accumulation of NFATc1 that was abolished by CsA treatment. Under differentiation conditions, intermittent CsA treatment enhanced gene expression of late osteoblastic differentiation markers and activator protein 1 (AP-1) family members. Superimposing flow upon CsA further enhanced expression of the AP-1 members Fra-1 and c-Jun. To delineate the contribution of NFAT in this response, cells were treated with VIVIT, a specific inhibitor of the calcineurin/NFAT interaction. Treatment with VIVIT blocked flow-induced nuclear NFATc1 accumulation but did not recapitulate the CsA-mediated enhancement of flow-induced AP-1 component gene expression. Taken together, our study is the first to demonstrate that CsA enhances mechanically-induced gene expression of AP-1 components in bone cells, and suggests that this response requires calcineurin-dependent mechanisms that are independent of inhibiting NFATc1 nuclear accumulation.